The Management and Adequacy of Road Infrastructure Expenditure for Economic Growth in Nigeria - Longe, J. B.; Omozuawo, M. B. (Prabandhan: Indian Journal of Management, 2013)
Transportation is a critical factor in the economic growth and development of any nation. Inadequate transportation limits a nation’s ability to utilize its natural resources, distribute foods and other finished goods, integrate the manufacturing and agriculture sectors and supply education, medical, and other infrastructural facilities. There is a need, therefore, to manage, maintain, and improve the existing transportation system and build new infrastructures for national wealth. It is on this bedrock that the present study assessed the management and adequacy of road infrastructure expenditure and economic growth in Nigeria considering the time period from 1980 to 2009. Descriptive analysis was used such as index growth rate based on simple averages on percentage growth on nominal and real values by deflating the nominal value to investigate the secondary data collected from the Central Bank of Nigeria. Findings revealed that expenditure on road construction and maintenance in Nigeria was not adequate when compared with other countries like USA, UK, France, Demark, Germany, India, etc. Nigeria’s government should, as a matter of prime importance, increase expenditure on road infrastructure and ensure that such expenditure is properly managed and supervised, and to generate additional revenue, the Government should encourage private initiatives in road funding.